A Study on the Use of Action Learning in Korean Language Education as a Foreign Language - An, Hee-Eun (Journal of Engineering Education Transformations, 2021)
This study is to review the methods of developing teaching materials that can enhance educational effect when Korean instructors teach grammar to foreign students in Korean language education and to practice the methods. The grammar in foreign language education is an important region that expands the expression of meaning and enables exact communication, so instructors spend a lot of time instruction grammar. Nevertheless, the reality is that instructors in the Korean language field are still limited in the existing conventional grammar teaching through textbooks. This study practices the teaching materials that can draw interest of learners and instill positive recognition to them for prospective Korean language instructors by combining a specific teaching method called Action Learning. This trial is valuable in that it can extend to various instruction methods instead of the existing conventional methods in Korean language education, and that learners can improve effective language acquisition and communication ability.